A sense of connectedness, transcendent experiences, and insights for compassionate action emerge through an international collective labyrinth walk with a shared intention during the COVID-19 pandemic - McGee, Jocelyn Shealy; Katzenmeyer, Christine; Boddie, Stephanie Clintonia; Meraz, Rebecca; Wood, Sinai (Frontiers in Psychology, 2023)
Introduction Labyrinth walking is an integrative contemplative practice that aims to engage the body, heart, mind, and spirit. In this article, qualitative findings from the first year of a mixed methods study on collective labyrinth walking with a shared intention are described. This form of labyrinth walking is distinct in that it is a social contemplative practice. It expands upon most of the labyrinth walking research to date which has been focused upon the individual. More specifically, practitioners walk labyrinths together in solidarity with the same intention in mind during collective labyrinth walking. This practice can be used locally (i.e. practitioners walk the same labyrinth together for the same reason) or non-locally (i.e. practitioners walk different labyrinths for the same reason together in different locations). The study is unique in that it took place at the height of the COVID-19 pandemic which was a time in recent history that evoked fear, uncertainty, grief, isolation, and disconnectedness for many persons around the world. Methods This sample in this study was comprised of 461 participants from 19 countries who collectively walked labyrinths together with a shared intention on World Labyrinth Day 2021. Most participants were women in middle to later life from the United States. Data was collected through an anonymous online survey and analyzed using the qualitative methodology of interpretive phenomenological analysis. Results Three predominant themes emerged from practitioners’ narrative accounts of their lived experiences: (1) multiple forms of connectedness (i.e., intrapersonal, interpersonal, transpersonal, labyrinth connection) were cultivated through collective labyrinth walking with a shared intention; (2) practitioners reported qualities associated with “transcendent” experiences during this experience (i.e., boundlessness, ultimacy, transcendence, connectedness, positive emotions); and (3) practitioners had insights for compassionate action. Discussion Findings suggest that collective labyrinth walking with a shared intention can contribute to individual and group flourishing during times of distress. Quasi-experimental and experimental research designs are needed to build on this exploratory developmental research and are described in this article.